2021
DOI: 10.1021/acsomega.1c00450
|View full text |Cite|
|
Sign up to set email alerts
|

Phase-Separating Binary Polymer Mixtures: The Degeneracy of the Virial Coefficients and Their Extraction from Phase Diagrams

Abstract: The Edmond−Ogston model for phase separation in binary polymer mixtures is based on a truncated virial expansion of the Helmholtz free energy up to the second-order terms in the concentration of the polymers. The second virial coefficients (B 11 , B 12 , B 22 ) are the three parameters of the model. Analytical solutions are presented for the critical point and the spinodal in terms of molar concentrations. The calculation of the binodal is simplified by splitting the problem into a part that can be solved anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 35 publications
(95 reference statements)
2
42
0
Order By: Relevance
“…In addition, eq is an expression for S c that explicitly shows that it satisfies the transformation ( B 11 , B 12 , B 22 , S c ) → ( B 22 , B 12 , B 11 , 1/ S c ). This property was already clear from eqs 20–21 in ref but was not obvious from the explicit solutions as presented in eqs 22–23 in ref .…”
Section: Practical Expression For the Slope Of The Tangent To Binodal...mentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, eq is an expression for S c that explicitly shows that it satisfies the transformation ( B 11 , B 12 , B 22 , S c ) → ( B 22 , B 12 , B 11 , 1/ S c ). This property was already clear from eqs 20–21 in ref but was not obvious from the explicit solutions as presented in eqs 22–23 in ref .…”
Section: Practical Expression For the Slope Of The Tangent To Binodal...mentioning
confidence: 77%
“…It was recently noted that eq 20 in ref , which expresses the stability requirement in the critical point where -S c is the slope of the tangent of the binodal and spinodal in the critical point and ( B 11 , B 12 , B 22 ) are the virial coefficients for the mixture can be rewritten as As a result, by using eqs 24 and 25 in ref , it is found that Here ( c 1, c , c 2, c ) are the coordinates of the critical point in molar concentration units. This is a useful relation in the case where the critical point is known.…”
Section: Practical Expression For the Slope Of The Tangent To Binodal...mentioning
confidence: 99%
See 3 more Smart Citations